Pemahaman Guru Pendidikan Agama Kristen tentang Mempersembahkan Tubuh Roma 12:1-3 - Andrianus Nababan (Jurnal Teologi Cultivation, 2020)
AbstrackThe Christian religious education teacher is an educator who provides knowledge about Christianity based on the Bible, centered on Jesus Christ, and relied on the Holy Spirit. Christian Religious Education teachers must be able to offer their bodies in Romans 12:1-3. The understanding of offering the body include: 1)the Christian religious education teacher always i approaches the loving and generous God 2)give advice by encouraging, directing convey the truth of God's Words. 3). renewal of the mind by distinguishing which is good and pleasing to God. Thus, each Christian religious education teacher can understand that a true educator must surrender his/her body as a true offering according to will of God.Key word: Christian education teacher; Offering the body Romans 12:1-3.ABSTRAKGuru Pendidikan Agama Kristen merupakan seorang pendidik yang memberikan ilmu pengetahuan tentang agama Kristen yang berdasarkan Alkitab, berpusat pada Yesus Kristus, dan bergantung pada Roh Kudus kepada peserta didik dalam kegiatan belajarmengajar. Guru Pendidikan Agama Kristen harus mampu mempersembahkan tubuhnya dalam Roma 12:1-3 sebagai ibadah sejati. Pemahaman mempersembahkan tubuh yaitu 1)guru Pendidikan agama Kristen senantiasa menghampiri Allah yang penuh kasih dan kemurahan 2)memberikan nasihat dengan mendorong, mengarahkan dan berdasarkan kebenaran Firman Tuhan. 3)pembaharuan budi dengan membedakan mana yang baik dan yang berkenan kepada Allah. Demikian Guru Pendidikan Agama kristen mampu memahami mempersembahkan tubuh menyangkut kehendak Allah sebagai pendidik yang sejati.Kata Kunci: Guru Pendidikan Agama Kristen; Mempersembahkan tubuh.